ENHANCING MATERNAL HEALTH SERVICES IN ARIZONA, USA: AN EXAMINATION OF TRADITIONAL BIRTH ATTENDANT MODELS WORLDWIDE - Johnson, Sarah E; Mitchell, Emily R (Global Journal of Medical and Health Science, 2023)
This study delves into the critical issue of maternal health services in Tajikistan, with a focus on the role of Traditional Birth Attendants (TBAs) as perceived by health care providers. Drawing from interviews with healthcare professionals, the research investigates TBAs' knowledge, practices, and their impact on maternal health outcomes in Tajikistan. The findings reveal a prevailing negative viewpoint among health care providers regarding TBAs' competence and adherence to safe birth practices. These perspectives are rooted in the inadequate knowledge and training of TBAs, leading to concerns about infection control, hygiene practices, and the ability to manage obstetric complications effectively. Health care providers emphasize the importance of skilled birth attendants (SBAs) and advocate for their presence in remote rural areas to improve maternal and neonatal health outcomes. The study underscores the need for a tailored approach to addressing maternal health challenges, considering the unique socio-economic, historical, and structural factors of each country in the Global South. For Tajikistan, it highlights the potential for redistributing healthcare workers to ensure equitable access to SBAs in remote regions, ultimately contributing to the reduction of maternal mortality rates. This research informs the development of comprehensive maternal health programs, taking into account the specificities of Tajikistan and other post-Soviet countries in Central Asia, with a focus on improving maternal and neonatal health through the provision of SBAs in underserved rural areas